?ADSORPTION STUDIES OF TARTARIC ACID FROM AQUEOUS SOLUTIONS ON CHARCOAL - KHAN, A. RASHEED; UDDIN, FAHIM; ALI, SALMA (Biological Sciences - PJSIR, 1994)
The adsorption of tartaric acid from aqueous solutions on the activated charcoal at 3D' was studied by titrometric method. The rate of adsorptions of tartaric acid on activated charcoal is higher at higher concentration of acid. Langmuir and Freundlich equations are well obeyed.